A laboratory examination of risky sexual behavior among female sexual trauma survivors. Issue 6 (22nd July 2022) - Mahoney, Colin T.; Lawyer, Steven R.; Pemberton, Shelby E.; Marchant, Kaitlyn M.
Abstract: Sexual violence against women is highly prevalent on college campuses. Survivors of sexual violence often engage in coping strategies such as risky sexual behavior. The present study used a behavioral task to measure sexual risk‐taking following experiences of positive or negative affect and an emotion suppression experimental manipulation. Sexually active adult female undergraduates ( N = 175) completed measures of sexual traumatization and affective experiences as well as an autobiographical recall task and a delay discounting task for hypothetical sexual outcomes. Half of the participants ( n = 87) were asked to suppress their emotional response to the autobiographical recall task. The findings indicate that sexual traumatization had a significant effect on risky sexual decision‐making, F (1, 167) = 23.27, p < .001, ηp 2 = .12, but affective condition, F (1, 167) = .57, p = .451, and emotion suppression, F (1, 167) = .69, p = .412, exhibited no significant associations with sexual risk‐taking. These findings suggest other factors may underlie the association between sexual trauma and risky sexual behavior, but further research is warranted.